A New Name in Pterocephalus (Caprifoliaceae) from Kurdistan-Iraq - Shahbaz, Saleem Shahbaz E.; Abozaid, Vameen (Science Journal of University of Zakho, 2020)
Pterocephalus tetraflorus S. E. Shahbaz, nom, nova, is proposed as a new name for Pterocephalus strictus Boiss. et Hohen, described by Boissier in1843, followed by Shahina and John in 2013. The description of P. tetraflorus is amended with characters of mature flowers and achenes, illustrated and its diagnostic characters, geographical distribution and habitats are presented. The species P. tetraflorus is closely related to P. strictus, but can be easily separated by forming only four-flowered capitula against numerous flowered-capitula for P. strictus and other Pterocephalus species.